Antecedents of the international association for accounting education and research (1966–1983): A review of early initiatives to develop an international academic accounting association. (3rd May 2019) - Clarke, Frank; Dean, Graeme; Persson, Martin
Abstract: Interest in this topic followed examination of new data discussing several antecedent proposals for establishing an international academic accounting association in the period 1966–1983, culminating in the 1984 formation of the International Association for Accounting Education and Research (IAAER). Relevant correspondence between several academics is now publicly available in the R.J. Chambers Archive at the University of Sydney. This enables justified statements to be made about the pre‐1984 antecedents of the IAAER, thereby filling a vacuum in our understanding of the history of the organization. We initially discuss Ray Chambers' and others' desire for, and attempts to promote an international approach to accounting research and practice. Chambers unsuccessfully attempted to organize an international think‐tank, beginning in the mid‐1960s with something like the International Economic Association of that time. He persisted, through participation in the Accounting Researchers International Association, an elite accounting society. Eventually, those proposals were discarded as he and others like Adolf Enthoven and David Solomons proposed an international confederation of accounting educators and researchers in 1977 and 1978. Efforts of other leading accounting academics of that time, in particular Norlin Rueschhoff and Seigo Nakajima, are also shown to have influenced the eventual formation of the simplified 1984 IAAER body with, initially, its individual‐based membership and objectives. Later, IAAER would become much more like the international confederation of accounting educators and researchers that Chambers had proposed in the 1997 Berlin International Conference on Accounting Education.